CONCEPT AND CLASSIFICATION OF ENGLISH PHRASEOLOGISMS AND THEIR SYNONYMS IN RUSSIAN (Academicia Globe: Inderscience Research, 2021)
The article is devoted to the definition of the national specifics of Russian and English phraseological units, their similarities and differences. The study was carried out within the framework of the comparative-parametric method using a number of formalized parameters.